1992
DOI: 10.1002/bjs.1800790221
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of lymph node metastases in patients with gastric cancer: evaluation of the Maruyama computer program

Abstract: The probability of survival of patients with gastric cancer depends upon depth of wall penetration by the primary tumour and metastatic lymph node burden. Radical lymphadenectomy may lead to prolonged survival but with increased morbidity. A computer program from Maruyama, National Cancer Centre, Tokyo enables evaluation of individual survival time and infiltration of lymph nodes. This analysis was applied to a German population. Computer-aided predictions were determined retrospectively using the prognostic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
2
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 19 publications
1
50
2
3
Order By: Relevance
“…24 Subsequent studies showed that although the sensitivity for lymph-node detection was high (97-100%), the specificity was very low (20%). 25 Recently, the gene expression profile of primary gastric cancer was applied to identify mRNAs associated with lymph node metastasis. 26 Marchet et al evaluated 5,541 genes in frozen tumor samples obtained from 32 patients with primary gastric adenocarcinomas (21 with lymph node metastasis and 11 without lymph node metastasis).…”
Section: Discussionmentioning
confidence: 99%
“…24 Subsequent studies showed that although the sensitivity for lymph-node detection was high (97-100%), the specificity was very low (20%). 25 Recently, the gene expression profile of primary gastric cancer was applied to identify mRNAs associated with lymph node metastasis. 26 Marchet et al evaluated 5,541 genes in frozen tumor samples obtained from 32 patients with primary gastric adenocarcinomas (21 with lymph node metastasis and 11 without lymph node metastasis).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Maruyama computer program can also be used to predict lymph node metastasis for patients with gastric carcinoma. Analysis of eight prognostic parameters such as gender, age, macroscopic type, location, position, diameter, histological classification, and depth of invasion using this computer program can gain the information on the expected frequency of metastasis in the 16 lymph node stations of each patient with gastric carcinoma [61,62] . However, to date, the prospective study for evaluating the accuracy of this computer program has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Based on recorded experience with actual patients, the likelihood of disease in 16 defi ned nodal stations around the stomach could be thus estimated. Performance of the so-called Maruyama program has been evaluated in German [2] and Italian populations [3] and found to be fairly accurate. For more than 15 years, the program has been used throughout the world as a tool to augment Japanese D-level guidelines with respect to lymph node dissection.…”
mentioning
confidence: 99%